Perancangan User Experience Pada Aplikasi Mobile Fasilitas Tanggap Bencana Dengan Pendekatan Metode Human-Centered Design (HCD) - Anderson Manurung; Herman Tolle; Muhammad Aminul Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Natural disasters are conditions of natural activity that can cause damage, and psychological disturbance to humans. Natural disasters can occur because of nature itself or human activities. Problems that often arise during the natural disaster evacuation process are uneven distribution of assistance, both in the form of logistics and the difficulty of determining the location of disaster response facilities to store emergency supplies is very important for the quality of service facilities provided after major emergencies, such as floods and tsunamis. This study aims to design how users can get user experience that can be used as needed in using information applications from emergency response centers. To produce good applications, various designs need to be done. The approach used is Human-centered Design (HCD). After getting a list of user needs and tasks, the design of solutions in the form of wireframe, information architecture and screenflow as the flow of user applications from the design of solutions is created using cognitive walkthrough with the user. This results in several problematic results, the results are corrected and re-evaluated according to the same method and refer to 4 cognitive walkthrough questions and the results of this study are the suitability of user experience design using HCD and the usability evaluation using cognitive walkthrough with users produces 91 % increase in usability and user experience, after being re-evaluated.